MDI versus CSII in Chinese adults with type 1 diabetes in a real-world situation: based on propensity score matching method - Yu, Jian; Wang, Hong; Zhu, Min; Xu, Jingjing (Health and quality of life outcomes, 2024)
Background Compared with multiple daily insulin injections (MDI), continuous subcutaneous insulin infusion (CSII) is significantly more expensive and has not been widely used in Chinese type 1 diabetes mellitus (T1DM) patients. So there are still significant knowledge gaps regarding clinical and patient-reported outcomes in China. Aims This study aims to compare the glycated hemoglobin (HbA 1C ), insulin therapy related quality of life (ITR-QOL), fear of hypoglycemia (FOH) of adult T1DM patients treated with MDI and CSII based on propensity score matching in real-world conditions in China. Methods Four hundred twenty adult T1DM patients who were treated with MDI or CSII continuously for more than 12 months in a national metabolic center from June 2021 to June 2023 were selected as the study subjects. Their QOL and FOH were evaluated with Insulin Therapy Related Quality of Life Measure Questionnaire-Chinese version (ITR-QOL-CV) and the Chinese Version Hypoglycemia Fear Survey-Worry Scale (CHFSII-WS), and their HbA 1C were collected at the same time. Potential confounding variables between the two groups were matched using propensity score matching. Results Of the 420 patients included in the study, 315 were in MDI group and 105 were in CSII group. 102 pairs were successfully matched. After matching, the total score of ITR-QOL-CV scale in CSII group was significantly higher than that in MDI group (87.08 ± 13.53 vs. 80.66 ± 19.25, P = 0.006). Among them, the dimensions of daily life, social life, and psychological state were all statistically different ( P < 0.05). The scores of CHFSII-WS (8.33 ± 3.49 vs. 11.77 ± 5.27, P = 0.003) and HbA 1C (7.19 ± 1.33% vs. 7.71 ± 1.93%, P = 0.045) in CSII group were lower than those in MDI group. Conclusions 25.0% of T1DM adults are treated with CSII. Compared with adult T1DM patients treated with MDI, those treated with CSII have higher ITR-QOL, less FoH, and better control of HbA 1C in real-world conditions in China. Therefore, regardless of economic factors, CSII is recommended for adult T1DM patients to optimize the therapeutic effect and outcomes.